Abortion - a subject that keeps coming back! - Mateusz Łakomski; Katarzyna Dudzik; Nataliia Badiuk (Kazimierz Wielki University, 2017)
Abortion is still a very popular and controversial topic in recent years. Many esteemed people in our country have confessed to abortion. The changes that had taken place through the amendment of the anti-abortion law [1] contributed to the confession of famous personalities [2]. Most of them show that it was not wrong. Most of the confessions of women who have made abortions come down to one sad conclusion: it is a decision that can not be reversed or changed. This decision imprints not only on the woman who takes her but also on the whole society. Especially since there is a solution for mothers who do not feel good to raise their child. There is even a window of life [28]. They usually work in children's homes, monasteries or hospitals. They allow anonymous leave of a child in a place that is safe for him or her. Children go to adoption and their parents are not sought. In almost allEuropethere are "windows of life". The United Nations Committee on the Rights of the Child, appealed for the elimination of "windows of life", the idea of which violates the child's right to identity and is not in accordance with the Convention on the Rights of the Child. The Committee expressed "deep concern over the lack of regulation and the increasing number of baby windows that allow for anonymous abandonment of the baby." Thus, another dilemma arises between the right to identity and the right to life. He recommends "anonymous birth" in hospitals. This is a procedure used inter alia inGermany. During childbirth, the mother remains anonymous, although her data is kept in a designated office. The child is 16 years old, if he wants to know her identity. [29]